Infection with the carcinogenic liver fluke Opisthorchis viverrini modifies intestinal and biliary microbiome. Issue 11 (7th August 2013) - Plieskatt, Jordan L.; Deenonpoe, Raksawan; Mulvenna, Jason P.; Krause, Lutz; Sripa, Banchob; Bethony, Jeffrey M.; Brindley, Paul J.
Abstract : Opisthorchis viverrini is a fish‐borne trematode endemic in East Asia. Following ingestion, the flukes locate to the biliary tree, where chronic infection frequently leads to cholangiocarcinoma (CCA). The mechanisms by which O. viverrini infection culminates in CCA remain unknown. An unexplored aspect is its influence on the host microbiome. In the hamster, infection with this pathogen reliably leads to CCA. Genomic DNAs of microbiota from colorectal contents and bile of hamsters and from whole O. viverrini were examined in this model of fluke‐induced CCA. Microbial communities were characterized by high‐throughput sequencing of variable regions 7–9 of prokaryotic 16S ribosomal DNA Of 1 million sequences, 536, 009 with useable reads were assignable to 29, 776 operational taxonomy units (OTUs) and, in turn, to 20 phyla and 273 genera of Bacteria or Archaea. Microbial community analyses revealed that fluke infection perturbed the gastrointestinal tract microbiome, increasing Lachnospiraceae, Ruminococcaceae, and Lactobacillaceae, while decreasing Porphyromonadaceae, Erysipelotrichaceae, and Eubacteriaceae ( P <0.05). More than 60 OTUs were detected in the biliary system, which confirmed bacteriobilia and a noteworthy community of microbes associated with the parasites. The fluke‐associated microorganisms included potential pathogens from the Enterobacteriaceae and Listeriaceae and others, including Cyanobacteria and Deinococci, usually found in external environments. Given that opisthorchiasis is distinguished from other helminth infections by a robust inflammatory phenotype with conspicuously elevated IL‐6, and that inflammation of the biliary system leads to periductal fibrosis, which is a precursor of CCA, the flukes and their microbiota may together drive this distinctive immune response.—Plieskatt, J. L., Raksawan, D., Mulvenna, J. P., Krause, L., Sripa, B., Bethony, J. M., Brindley, P. J. Infection with the carcinogenic liver fluke Opisthorchis viverrini modifies intestinal and biliary microbiome. FASEB J . 27, 4572–4584 (2013). www.fasebj.org